Emerging Role of Schwann Cells in Neuropathic Pain: Receptors, Glial Mediators and Myelination - Wei, Zhongya; Fei, Ying; Su, Wenfeng; Chen, Gang (Frontiers in Cellular Neuroscience, 2019)
Neuropathic pain caused by nerve injury or disease remains a major challenge for modern medicine worldwide. Most of the pathogenic mechanisms underlying neuropathic pain are centered on neuronal mechanisms. Accumulating evidence suggests that nonneuronal cells, especially glial cells, also play active roles in the initiation and resolution of pain. The preponderance of evidence has implicated central nervous system glial cells, i.e., microglia and astrocytes, in the control of pain. The role of Schwann cells in neuropathic pain remains poorly understood. Schwann cells, which detect nerve injury and provide the first response, play a critical role in the development and maintenance of neuropathic pain. The cells respond to nerve injury by changing their phenotype, proliferating and interacting with nociceptive neurons by releasing glial mediators (growth factors, cytokines, chemokines, and biologically active small molecules). In addition, receptors expressed in active Schwann cells have the potential to regulate different pain conditions. In this review, we will provide and discuss emerging evidence by integrating recent advances related to Schwann cells and neuropathic pain.